Forskrift om regulering av fiske med norske fartøyer i Antarktis (CCAMLR-området) - fiskeridepartementet, Nærings- og (Lovdata, 1998)
Keywords: Sørishavet; fiskeri; jus

Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Nitrogen uptake in the infiltration community, an ice algal community in Antarctic pack-ice - Kristiansen, Svein; Farbrot, Tove; Kuosa, Harri; Myklestad, Sverre M; Quillfeldt von, Cecilie Hellum (Polar Biology, 1998)
An infiltration community was the dominating ice algal community in pack-ice off Queen Maud Land, Southern Ocean, in January 1993. The community was dominated by autotrophic processes, and the most common species were the prymnesiophyte Phaeocystis antarctica and the diatoms Chaetoceros neglectus and Fragilariopsis cylindrus. The concentration of chlorophyll a was 1.3–47.9 μg l−1, and the inner part of the community was nitrate depleted. Uptake rates of nitrate, nitrite, ammonium, urea and amino acids were measured using 15N. Nitrate was the major nitrogen source for ice algal growth (67 ± 6% nitrate uptake). It is suggested that % nitrate uptake in the infiltration community decreases during the growth season, from 92% during spring (literature data) to 67% during summer. Scalar irradiance in the infiltration community was high and variable. It reached ca. 2000 μmol m−2 s−1 at some locations, and nitrate uptake rate was potentially photoinhibited at irradiances >500 μmol m−2 s−1. Nitrate uptake rate in an average infiltration community (0.6 m of snow cover) was lowered by 13% over a 2-week period due to photoinhibition.
Keywords: Sørishavet; Weddellhavet; alger; marin biologi

Establishing chronologies from acid-insoluble organic 14C dates on Antarctic (Ross Sea) and Arctic (North Atlantic) marine sediments - Licht, Kathy J; Cunningham, Wendy L; Andrews, John T; Domack, Eugene W; Jennings, Anne E (Polar Research, 1998)
Keywords: Rosshavet; Sørishavet; paleoseanografi; polarområdene; sedimentologi

Gut length, food transit time and diving habit in phocid seals - Mårtensson, Per-Erik; Nordøy, Erling; Messelt, Edward; Blix, Arnoldus Schytte (Polar Biology, 1998)
Keywords: Sørishavet; seler; zoologi

Snipp snapp snute... : beretning om livet om bord i hvalbåtene fra Vestfold på fangstfeltene i Sydishavet - Østevik, Tore (Færder forlag, 1998)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Døde menn vender tilbake: Shackletons høyst private Whitbread-seilas - Winge, Jon (Norsk sjøfartsmuseum. Årbok, 1998)
Keywords: Endurance (skip); Ernest Henry Shackleton; Sørishavet; ekspedisjoner; oppdagelsesreiser; skipsfart